PENGARUH KEADILAN ORGANISASIONAL, KOMITMEN ORGANISASI, DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PABRIK ES AQUA BISNIS PROBOLINGGO - Fandy Alawi Mustofa; Arnis Budi Susanto; Ema Desia Prajitiasari; Purnamie Titisari; Almas Farah Dinna Dewi (Study Program of Management Faculty of Economics and Business University of Jember, 2022)
This article aims to analyze the effect of organizational justice, organizational commitment dan job satisfaction toward organizational citizenship behavior (OCB) in Ice Factory Aqua Bisnis Probolinggo.This study used sample of 36 respondent taken using the saturation sampling technique. Data were analyzed using multiple linier regression. The results of this study showed that organizational justice, organizational commitment and job satisfaction have a positive effect and significan on organizational citizenship behavior (OCB).